Efficacy of Dried Distiller’s Grains with Solubles as a Replacement for Soybean Meal in the Rations of Growing Goats - Sihag, Sajjan; Sihag, Zile Singh; Shunthwal, Jyoti; Kumar, Sushil (Indian Journal of Animal Nutrition, 2017)
The effect of replacement of soybean meal (SBM) by dried distiller’s grains with solubles (DDGS) at different levels in the concentrate mixture on growth performance and nutrient utilization in goat’s kids was studied. Twenty four crossbred weaned female crossbred kids (4-5 mon.) with an average body weight 10.63±0.67 kg were divided into four groups of six animals each. All the kids were fed gram straw ad lib. and weighedquantity of concentrate mixture as per their nutrient requirements. The concentrate mixture (% parts: maize 50, barley 19, soybean meal 28, mineral mixture 2 and common salt 1) was fed to control group (T1) while SBM of control group was replaced with DDGS @ 50, 75, and 100% (CP basis) in the concentrate mixture of groups T2, T3 and T4, respectively. The experiment lasted for 120 days. A digestion trial of 6 d duration was conducted at the end of the study. Average DM intake (DMI) during the feeding trial was 458, 456, 455 and 457 g/d in groups T1, T2, T3 and T4, respectively and DMI as percent of body weight was 2.93, 2.85, 2.94 and 2.94 in the respective groups revealing that DMI was not affected by different levels of DDGS. Average daily gain (ADG) was 58.7,59.7, 57.6 and 56.0 g in groups T1, T2, T3 and T4, respectively. The daily weight gain and total weight gain by the goat kids were also not affected up to 75% replacement level but decreased (P